Uji Coba Horisontal Axis Wind Turine Tipe Blade Tapperless Naca 4412 Menggunakan Wind Lens - Achmad Wardana; Muhammad Halil; Niharman Niharman (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2022)
Abstract Renewable energy is one of the alternative energies for the application of effective energy in the future because it also takes into account the increasing dependence of humans on the use of fossil energy which will reduce the availability of fossil energy and renewable energy can also be used as an alternative energy source whose distribution is For areas that have not been reached by PLN because of the large and centralized power generation system, one solution is the use of renewable energy generation, one of which is wind energy. Wind energy generators have the advantage that the energy costs are relatively cheaper, but the challenge is that this plant is designed for areas with medium and high wind speed groups so that the performance of this plant will decrease when applied in low pressure areas, so optimization is needed on the wrong design. The only thing is the addition of a shroud (wind lens) on a wind turbine that can increase performance twice as much as a wind turbine without a wind lens. For the test, a wind turbine design test variable was carried out using a windlens and a wind turbine without a wind lens with wind speeds of 3 m/s, 4 m/s and 5 m/s. The best test results used a windlens Cp max = 0.898 and Ct max = 0.58 at a wind speed of 3 m/s.